Murder your employer the McMasters guide to homicide - Holmes, Rupert; Louizos, Anna (New York Avid Reader Press, 2023)
"Preparing you for an education you'll never forget, this introduction to The McMasters Conservatory, dedicated to the consummate execution of homicidal arts, follows students as they prepare for graduation by getting away with the perfect murder of someone whose death will make the world a much better place to live"--
Who hasn't wondered for a split second what the world would be like if a person who is the object of your affliction ceased to exist? But then you've probably never heard of The McMasters Conservatory, dedicated to the consummate execution of the homicidal arts. To gain admission, a student must have an ethical reason for erasing someone who deeply deserves a fate no worse (nor better) than death. The campus of this "Poison Ivy League" college--its location unknown to even those who study there--is where you might find yourself the practice target of a classmate...and where one's mandatory graduation thesis is getting away with the perfect murder of someone whose death will make the world a much better place to live.
111266
Keywords: Murder -- Fiction; Schools -- Fiction; Secret societies -- Fiction; Industrial relations -- Fiction; Detective and mystery fiction; Humorous fiction; Thrillers (Fiction); Novels